IMPACT OF SEA WATER INTRUSION TO GROUND WATER WELLS IN SASAK VILLAGE SASAK RANAH PASISIE DISTRICT PASAMAN BARAT REGION - VIVI YONA, RESCA; Drs. Dasrizal, MP, Drs. Dasrizal, MP; Prari Keslan, Widya (STKIP PGRI Sumbar, 2014)
This study aims to 1) the impact of the condition of shallow ground water wells to chemicalc aused by the intrusion of sea water to the ground water wells, 2) the impact of the condition of the shallow ground water wells physical caused by the intrusion of sea water to the ground water wells and 3) public efforts to prevent sea water intrusion impacts on ground water wells in Sasak village Sasak Ranah Pasisie district Pasaman Barat Region.The results showed that: (1) the impact of seawater intrusion on the condition of shallow ground water wells be seen from the chemical properties, the amount of magnesium ranged from 1,835 to 2,626 mg / L, the intrusion of sea water had no impact of magnesium, iron ranged from 0,058 to 0,276 mg / L, mean seawater intrusion had no impact on the content of iron (Fe) shallow ground water wells. Total manganese ranged from 0,0038 to 1,193 qualify for drinking water, sea water intrusion means no impact. pH of water ranged 5,0 -5,72 51 that qualifies for drinking water, salinity ranged from 15,46 to 81,92, (2) the impact of seawater intrusion to shallow ground water wells views of physical properties, the temperature of the water wells ranged between 360C - 390C. (3) Public efforts prevent seawater intrusion in various ways, such as by digging deeper wells, plant trees and do not consume water that has been exposed to sea water intrusion.